PENGARUH STRATEGI EXPERIENTAL MARKETING DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KAOS DAGADU - Gilang, Indiriy; EP, Apriatni; Widayanto, Widayanto (Jurnal Ilmu Administrasi Bisnis, 2016)
This study aimed to test the influence of experiental marketing strategy and product quality on purchasing decision of T-Shirt Dagadu in Yogyatourium outlet of PT. Aseli Dagadu Djokdja. The samples in this research are 100 consumers who shop Dagadu T-Shirt in Yogyatourium outlet. The author used SPSS 16.0 program to test the regression on data analysis. And the study results indicate that experiental marketing strategy has a positive and significant influence on the purchasing decision, with coefficient determination is 5,9%, product quality has a positive and significant influence on the purchasing decision, with coefficient determination is 12,2%, and experiental marketing strategy and product quality have a positive and significant influence on the purchasing decision, with the coefficient determination is 20,8%. Results of this study indicate that in the order to enhance the purchasing decision, PT. Aseli Dagadu Djokdja should consider the experiental marketing strategy and product quality.